Comparative Analysis of Moor Frog Anomalies (Rana arvalis Nils., 1842) in Different Areas of Surgut City - Ibragimova, D V; Nakonechnyi, N V (KnE Life Sciences, 2018)
In the local populations of moor frogs in Surgut city, 30 types of morphological anomalies were discovered. The quantity and frequency of anomalies were high in industrial and multistoried areas of the city. Individual subjects could have 1 to 4 different anomalies. The paper reveals that major variations in anomalies occurs in industrial and multistoried areas of the city.